Propuesta de laboratorio de computación para primero, segundo y tercero de bachillerato de la unidad educativa Fiscomisional “José María Vélaz” extensión educativa nº 1. - Uchuari Puglla, Diego Fernando (2016)
This thesis research refers to a: PROPUESTA DE LABORATORIO DE COMPUTACIÓN PARA PRIMERO, SEGUNDO Y TERCERO DE BACHILLERATO DE LA UNIDAD EDUCATIVA FISCOMISIONAL “JOSÉ MARÍA VÉLAZ” EXTENSIÓN EDUCATIVA Nº 1., same which was developed according to the requirements of Academic System of the National University of Loja, and as a requirement to qualify for the Degree in Educational Computing. The central problem was: Can you improve the teaching process - learning by implementing a computer lab, Education Unit Fiscomisional "José María Vélaz" educational outreach Nº 1. Loja? He raised the following general objective: Develop a proposal to implement a computer lab for first, second and third high school of the Education Unit Fiscomisional "José María Vélaz" educational outreach Nº 1. Loja. The methods used for the preparation of this thesis research was: scientific, deductive, inductive, descriptive, and statistical same model that served efficiently help meet the proposed research. The techniques and instruments applied were: direct observation to the school to verify existing problems to implement a computer lab, the survey of students to evaluate how it is developing the teaching-learning process and requirements for development computer lab, and interview teachers to meet the difficulties in the computer field. According to the results of the survey of students, 62% have few computer skills, while 22% do not have any knowledge, and 16% if you have computer skills, plus 87% of students report that there are no proposals for the development of a computer lab and 3% say yes, also according to the interview applied to teachers fully agree that a computer lab help in classroom activities, so that students gain significant learning computer. It is recommended to the authorities of the institution take the necessary steps to implement computer lab, teachers and students to continuously monitor for the implementation of the proposal, in addition to the authorities of the school management training for administrative staff , teachers and students in the computer field.